2015
DOI: 10.1007/s40279-015-0334-7
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Snow-Sports Injury Risk Factors and Countermeasures: A Meta-Analysis Review and Haddon Matrix Evaluation

Abstract: Snow sports injuries risk factors and countermeasures 2 listed above qualify for authorship based on making one or more of the substantial contributions to the intellectual content of the manuscript.The opinions expressed are those solely of the authors and do not necessarily reflect those of the Accident Compensation Corporation, New Zealand. Abstract Background:Snow sports (alpine skiing/snowboarding) would benefit from easily implemented and cost effective injury prevention countermeasures that are effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 127 publications
0
44
0
1
Order By: Relevance
“…As noted in previous systematic reviews [31], the usual method of quality evaluation comprises tools such as the Delphi [32] or PEDro (Physiotherapy Evidence Database) [33] scales whose criteria are often not relevant for specific review study types, including this current review article. For example, similar to Hume et al [31], 5 of the 11 PEDro scale criteria were not included by any study in this review, including concealed allocation, subject blinding, therapist blinding, assessor blinding and intention-to-treat analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted in previous systematic reviews [31], the usual method of quality evaluation comprises tools such as the Delphi [32] or PEDro (Physiotherapy Evidence Database) [33] scales whose criteria are often not relevant for specific review study types, including this current review article. For example, similar to Hume et al [31], 5 of the 11 PEDro scale criteria were not included by any study in this review, including concealed allocation, subject blinding, therapist blinding, assessor blinding and intention-to-treat analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For example, similar to Hume et al [31], 5 of the 11 PEDro scale criteria were not included by any study in this review, including concealed allocation, subject blinding, therapist blinding, assessor blinding and intention-to-treat analysis. Therefore, to reduce the risk of bias, and given the unsuitability of scales such as Delphi and PEDro to assess the literature in this review, two authors independently evaluated each included article using a 9-item custom methodological quality assessment scale with scores ranging from 0 to 2 (total score out of 18).…”
Section: Methodsmentioning
confidence: 99%
“…In Übereinstimmung mit der Studie von Hildebrant et al [5] zeigten Anfänger die geringste Häufigkeit an richtigen Antworten. Dies ist insofern relevant, da Ski-und Snowboardanfänger ein erhöhtes Verletzungsrisiko aufweisen [6]. Entsprechend sollte die Vermittlung von sicherheitsrelevantem Wissen beispielsweise in Skikursen von Skischulen aber auch durch Informationskampagnen von Skiliftbetreibern besonders die Gruppe der Anfänger ansprechen.…”
Section: Diskussionunclassified
“…As concluded in the systematic review of Hume et al ,19 using Haddon’s prevention concepts, the design of TPs should consider prevention of injuries. Research related to playground and skatepark injuries has demonstrated an association between the quality of the physical environment and the risk of injury,31–34 and this may also be true for TPs.…”
Section: Introductionmentioning
confidence: 99%